Myocardial localization of coronavirus in COVID‐19 cardiogenic shock - Tavazzi, Guido (Eur J Heart Fail, 2020)
We describe the first case of acute cardiac injury directly linked to myocardial localization of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in a 69‐year‐old patient with flu‐like symptoms rapidly degenerating into respiratory distress, hypotension, and cardiogenic shock. The patient was successfully treated with venous‐arterial extracorporeal membrane oxygenation (ECMO) and mechanical ventilation. Cardiac function fully recovered in 5 days and ECMO was removed. Endomyocardial biopsy demonstrated low‐grade myocardial inflammation and viral particles in the myocardium suggesting either a viraemic phase or, alternatively, infected macrophage migration from the lung.